PROMOTIONAL STRATEGY THROUGH THE UTILIZATION OF INSTAGRAM SOCIAL MEDIA TO INCREASE SALES VOLUME (A CASE STUDY ON CUTA HOUSE COFFEE SHOP SURABAYA) - Santi Eka Rahmawati; Indah Respati Kusumasari (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to analyze the effectiveness of promotional strategies carried out through the utilization of Instagram social media in increasing sales volume at Cuta House Coffee Shop Surabaya. A qualitative approach was employed, with data collected through in-depth interviews with 10 respondents, direct observations, and sales documentation. The findings reveal that Instagram-based promotional strategies have been implemented effectively, as evidenced by an increase in the company’s revenue along with higher sales volume. Analysis of internal and external environmental factors identified ten internal factors, with key strengths including diverse promotional types, attractive offers, excellent service and product quality, and online business implementation. Additionally, eight external factors were found to influence opportunities and threats in the business environment. The results of IFAS and EFAS calculations indicate total scores of 3.38 for strengths, 2.35 for weaknesses, 3.10 for opportunities, and 1.82 for threats. SWOT matrix mapping positions Cuta House’s strategy in quadrant I with coordinates (X;Y) (1.03; 1.28), indicating an aggressive strategic approach. Therefore, leveraging internal strengths to capitalize on market opportunities is a strategic action that can sustainably enhance sales volume.